82‐3: Temporary Bonding Alternative to Laser Lift‐Off for Flexible Displays. Issue 1 (30th May 2018) - Reit, Radu; Espinoza, Jesus; Vega, Abraham; Voutsas, Tolis; Avendaño-Bolívar, Adrian; Arreaga-Salas, David
Abstract : A new material, ATB, is demonstrated as a temporary bonding layer for a poly(amic acid)‐based, solution‐cast polyimide and Pylux‐MF, a polysulfide thermoset. Both films are deposited atop carriers coated with ATB and after device definition, are removed from the carriers using a 90° tensile peel with peel strengths below 10 cN/cm.